Simulation and analysis performance of BPSK, QPSK and 8-PSK by using convolutional coding for WCDMA environment / Mastura Murat - Murat, Mastura (2010)
This thesis illustrates the simulation and performance analysis of BPSK, QPSK and 8- PSK by using convolutional coding for WCDMA environment. The model consists of the transmitter, transmission channel and also the receiver. The main objective of this project is to compare and identify which system produced better result by analyzing the performance of the channels in terms of the bit error rate, BER. This project is using Matlab as the simulation tools. The simulation used three modulation techniques where first technique used BPSK second is QPSK and 8-PSK is for the third modulation technique. Convolutional codes were applied to the multichannel modulation system to encode and decode the signals in the channels before modulation and after demodulation processes in the system. As for the noise, AWGN was being injected to the WCDMA spread spectrum environment. Even though QPSK and 8-PSK provides more data capacity compare to BPSK, but from the result obtain BPSK gives a better BER performance compared to QPSK and 8-PSK